Could mandatory vaccination increase coverage in health-care Workers? The experience of Bari Policlinico General Hospital. Issue 12 (2nd December 2021) - Di Lorenzo, Antonio; Tafuri, Silvio; Martinelli, Andrea; Diella, Giusy; Vimercati, Luigi; Stefanizzi, Pasquale
ABSTRACT: Influenza is a major issue for health-care systems all over the world and health-care workers (HCWs) are a subgroup at increased risk of exposure to respiratory pathogens, including influenza, with potential threat for both their own and their patients' health. Despite this and despite the anti-influenza vaccination being offered to all HCWs, vaccination coverage among them is still low in Europe, generally less than 30%. During 2020s influenza season, influenza vaccination begun mandatory in Puglia (Italy) and Bari Policlinico General Hospital designed an active call system in order to increase its employees' compliance to vaccination. This system was able to determine an increase of vaccination coverage from 23.1% to 77.6%.